Higher Education Learning Experiences Pre-, Peri- and Post-COVID-19: What Will Evolve, and What Will Survive? - Mark Warnes; Simon Pratt-Adams; Claire V. S. Pike (SAGE Open)
This article reports the results of a mixed-methods research project at one UK university to explore student experiences before, during, and after the COVID-19 lockdowns. The research questions were ‘Which HE learning experiences will be retained?’ and ‘Which HE learning experiences will evolve?’. All final-year undergraduates in the 2021/22 academic year ( n = ~3,000) were asked, via a survey and focus groups, to rate various formats of learning and teaching for their effectiveness for learning, building positive learning communities, and overall satisfaction. Students were also asked to list any features of their learning from before the pandemic that the University should reinstate, and any from during the pandemic that should be retained. Quantitative data were analysed using SPSS, and qualitative data were analysed using NVivo. Analysis suggests that prior to the lockdowns, students felt they had the full ‘university experience’ as they had anticipated. During lockdowns, students faced disorientation, isolation, and a lack of motivation, but appreciated not having to commute, and an improved work/life balance. After lockdown ended, students wanted to return to on-campus teaching, particularly for the social aspects, and to experience higher-quality teaching. Although large-group lectures on campus scored highly for both effectiveness and satisfaction, students wanted to retain recordings of live lectures for revision and unanticipated absences. Analysis by demographics indicated variations by gender, study mode (i.e. Part-Time/Full-time), learning difficulties, and caring responsibilities, emphasising the imperative to meet the differing learning needs of diverse student populations.